Improving Scientific Argumentation in University Students Through a Training Approach - Rohayati, Rohayati; Syihabuddin, Syihabuddin; Anshori, Dadang; Sastromiharjo, Andoyo (KnE Social Sciences, 2024)
The capacity to recognize formal arguments is crucial for clinical literacy. However, college students frequently lack a structural understanding of those arguments, in particular when the arguments are extra complicated. This study used an experimental method with a pre-post-check design. A follow-up of four weeks was used to research whether courses on figuring out the structural additives of casual arguments would enhance college students’ competence to recognize complicated arguments. The course was embedded in a constructivist mastering surroundings, and its content material was primarily based totally on Toulmin’s argument shape model, consistent with which arguments may be deconstructed into numerous purposeful additives: claims, datums, warrants, helping evidence, and rebuttals. Being capable of discovering warrants was primary to clinical literacy due to the fact warrants decide whether an end was justified primarily based totally on data. The effects display that schooling in argument shape typically no longer enhances overall recital for all college pupils and argument kinds, however, it’s miles beneficial for figuring out extra complicated arguments with much less specific systems and relational components among key additives (i.e. warrants). High-reaching college students gain maximum from this intervention, and it additionally enables college students with excessive pretest correctness scores. Our effects advocate that interferences to sell argumentation abilities need to be included in the curriculum, and those interventions need to be designed to shape the skill degree of learners. Keywords: Scientific Argumentation, University Students, Training Approach